The Host-Pathogen Interactions and Epicellular Lifestyle of Neisseria meningitidis - Mikucki, August; McCluskey, Nicolie R.; Kahler, Charlene M. (Frontiers in Cellular and Infection Microbiology, 2022)
Neisseria meningitidis is a gram-negative diplococcus and a transient commensal of the human nasopharynx. It shares and competes for this niche with a number of other Neisseria species including N. lactamica, N. cinerea and N. mucosa. Unlike these other members of the genus, N. meningitidis may become invasive, crossing the epithelium of the nasopharynx and entering the bloodstream, where it rapidly proliferates causing a syndrome known as Invasive Meningococcal Disease (IMD). IMD progresses rapidly to cause septic shock and meningitis and is often fatal despite aggressive antibiotic therapy. While many of the ways in which meningococci survive in the host environment have been well studied, recent insights into the interactions between N. meningitidis and the epithelial, serum, and endothelial environments have expanded our understanding of how IMD develops. This review seeks to incorporate recent work into the established model of pathogenesis. In particular, we focus on the competition that N. meningitidis faces in the nasopharynx from other Neisseria species, and how the genetic diversity of the meningococcus contributes to the wide range of inflammatory and pathogenic potentials observed among different lineages.